ISSUES ON DISABILITY ADVERTISING IMAGING IN MEDIA - Nebojsa Randjelovic; Danica Pirsl; Tea Pirsl (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
A great many government organizations, charities, advocacy groups, consulting firms and media organizations are expending enormous amounts of resources because they all agree with the premise that media are a powerful educator for cultural values and attitudes. Social learning theory, cultivation and media dependency theory all support that premise, as does a body of work in the rehabilitation literature. In the small world of advertising the results of this study suggest that images of people with disabilities in advertising are a bigger part of the overall advertising environment than they were in 2001 despite the difficulties associated with contextual elements in an ad, and the public outrage/civil suits. But if we compare the appearance rate for AI advertising, as part of the total advertising environment, to the percentage of adults classified as disabled in the total U.S. population based, people with disabilities are very much under-represented (1.7% from this study as compared to 12% according to the 2009 Disability Compendium). If equal representation is the goal, we are not there yet. If acceptance of the use of disabled portrayals in general product advertising on the part of the advertising industry is the goal, then much progress has been made.